2021
DOI: 10.1111/1467-923x.13005
|View full text |Cite
|
Sign up to set email alerts
|

The Politics of Levelling Up

Abstract: ‘Levelling up’ is an expression of a realignment in British politics with the Conservatives presenting themselves as the new party of redistribution. This is not primarily concerned with redistribution between social classes, or even between regions, but rather targets communities that feel they have lost their centrality and standing. This seemingly surprising manoeuvre is facilitated by voters’ distrust of politics, a geography of discontent that reflects uneven patterns of social and economic development, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(19 citation statements)
references
References 0 publications
0
19
0
Order By: Relevance
“…Fundamentally, not only is the sub-regional institutional framework in England under-developed, but the Treasury’s grip over borrowing through financial control and economic management greatly diminishes the discretion and room for manoeuvre of local actors. Levelling up funding is heavily centralised and controlled by the Treasury alongside the MHCLG (Jennings et al, 2021). The Westminster system of government is more generally characterised by centralisation, top-down decision-making, and hierarchy accompanied by the fragmented administrative landscape at the sub-regional level with a multiplicity of organisations divided by overlapping responsibilities and powers – as this study of the Structural Funds and regional economic development has demonstrated (Rhodes, 2005; Warner et al, 2021).…”
Section: Results and Analysismentioning
confidence: 99%
“…Fundamentally, not only is the sub-regional institutional framework in England under-developed, but the Treasury’s grip over borrowing through financial control and economic management greatly diminishes the discretion and room for manoeuvre of local actors. Levelling up funding is heavily centralised and controlled by the Treasury alongside the MHCLG (Jennings et al, 2021). The Westminster system of government is more generally characterised by centralisation, top-down decision-making, and hierarchy accompanied by the fragmented administrative landscape at the sub-regional level with a multiplicity of organisations divided by overlapping responsibilities and powers – as this study of the Structural Funds and regional economic development has demonstrated (Rhodes, 2005; Warner et al, 2021).…”
Section: Results and Analysismentioning
confidence: 99%
“…Undone by his own hubris and the burning desire for revenge of his former closest advisor, Dominic Cummings, Johnson has, to the frustration of his sympathisers, tossed away the chance to embed a realignment of British politics to Conservative electoral advantage. This failure is most obviously manifest in his much-trumpeted levelling up agenda, which remains beset with inconsistencies and has yet to evolve from an effective political slogan into a coherent policy programme (Jennings et al 2021; Newman, 2021).…”
Section: Existential Crisismentioning
confidence: 99%
“…Retaining local and subnational state capacity in the face of fiscal pressures will be the key if government is to recommit to and accelerate policies to boost economies in lagging and left behind places including those in the Northeast, Tees Valley and the East Midlands. This was initially absent from the language of Levelling Up whose early focus was on short term, physical capital and infrastructure projects (Jennings et al, 2020). The Levelling Up White Paper (HMG, 2022) now acknowledges that local government funding has been over reliant on bidding for funding and offers some initial thoughts about place-based budgets.…”
Section: Contextualising Multi-level Governancementioning
confidence: 99%